Spectrophotometric Determination of Thioridazine Hydrochloride in Tablets and Biological Fluids by Ion-Pair and Oxidation Reactions. Issue 3 (3rd June 2012) - El-Didamony El-Didamony, Akram Akram; Hafeez Hafeez, Sameh Sameh
Abstract : Two simple, sensitive and selective spectrophotometric methods have been described for the determination of the psychoactive drug, thioridazine HCl in tablets and in biological fluids. The first method is based on the oxidation of thioridazine HCl with measured excess of KMnO4 under acidic conditions followed by the determination of unreacted oxidant using indigo carmine and methyl orange. The second method is based on the formation of ion-pair complexes with the acidic sulphophthalein dyes such as bromocresol green and bromocresol purple at pH 1.8 of KCl-HCl buffer. The formed complexes were extracted into methylene chloride and their absorbance was measured at 412 nm. Optimizations of the different experimental conditions are described for both methods. The proposed methods were successfully applied for determination of the drug in tablets and biological fluids with good accuracy and precision. Statistical comparison of the results with those obtained by an official method showed good agreement and indicated no significant difference in accuracy and precision.